2014
DOI: 10.1111/jce.12514
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Near Real‐Time Lesion Assessment During Radiofrequency Catheter Ablation in Humans Using Acoustic Radiation Force Impulse Imaging

Abstract: Background Visual confirmation of radiofrequency ablation (RFA) lesions during clinical cardiac ablation procedures could improve procedure efficacy, safety, and efficiency. It was previously shown that acoustic radiation force impulse (ARFI) imaging can identify RFA lesions in vitro and in vivo in an animal model. This is the “first-in-human” feasibility demonstration of intracardiac ARFI imaging of RFA lesions in patients undergoing catheter ablation for atrial flutter (AFL) or atrial fibrillation (AF). Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Finally, ARFI imaging has been successfully adapted to clinical ultrasound and mapping systems during routine clinical catheter ablation procedures with demonstrated feasibility of acquiring ARFI images of radiofrequency lesions from clinically by guest on May 12, 2018 http://circep.ahajournals.org/ Downloaded from relevant ablation target regions in both the right and the left atria ( Figure 4). 73 Although ARFI imaging shows promise as a tool to evaluate cardiac ablation lesions in situ, and has potential to offer a new and complimentary procedure end point for therapeutic ablation by providing direct information about whether a radiofrequency lesion set is complete (contiguous and transmural lesions without gaps), further development of imaging catheters to enhance imaging depth and studies to establish the role of this technology in clinical practice are needed.…”
Section: Acoustic Radiation Force Impulse Imagingmentioning
confidence: 99%
“…Finally, ARFI imaging has been successfully adapted to clinical ultrasound and mapping systems during routine clinical catheter ablation procedures with demonstrated feasibility of acquiring ARFI images of radiofrequency lesions from clinically by guest on May 12, 2018 http://circep.ahajournals.org/ Downloaded from relevant ablation target regions in both the right and the left atria ( Figure 4). 73 Although ARFI imaging shows promise as a tool to evaluate cardiac ablation lesions in situ, and has potential to offer a new and complimentary procedure end point for therapeutic ablation by providing direct information about whether a radiofrequency lesion set is complete (contiguous and transmural lesions without gaps), further development of imaging catheters to enhance imaging depth and studies to establish the role of this technology in clinical practice are needed.…”
Section: Acoustic Radiation Force Impulse Imagingmentioning
confidence: 99%
“…Other groups demonstrated the feasibility of similar techniques with the same approach [13,14]. However this approach necessitates the use of two catheters, one for ablation and one for ultrasonic monitoring.…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, multiple groups have now shown that deformability as indexed by these techniques drops immediately following RF ablation in vivo. (Bahnson et al, 2014; Kwiecinski et al, 2014) Interestingly, this shear stiffness is quite stable from 2-30 minutes after ablation in the center of the lesion, while the stiffness of adjacent myocardium increases more slowly; (Eyerly et al, 2015) Eyerly et al suggested that the immediate response may reflect changes in tissue properties due to thermal damage, while the slower response in adjacent tissue reflects edema. (Eyerly et al, 2015) Less is known about the evolution of mechanical properties beyond the first few minutes post-ablation, other than the fact that scar tissue forms in damaged regions and is presumably stiffer than the surrounding myocardium.…”
Section: Ablation Of Atrial Fibrillationmentioning
confidence: 99%